(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The brick production sector in India depends upon fuel wasting units and techniques, which contribute to air pollution and emission of greenhouse gases, thus generating negative economic and environmental impacts. Besides, within the sector there are social dilemmas such as bonded labour, child labour, work-place adverse living environment, unhygienic water and sanitation conditions, poor education and adverse occupational health conditions etc., all of these problems need serious consideration. Various designated public sector organizations are responsible for compiling statistics from a number of pre-determined sources. The statistical information usually responds to policy makers’ requirements in different government departments. The available survey reports reveal that they are blind on various social indicators related to human vulnerabilities. For example, the labour force surveys do not have indices related to labour bondage.